Redo men ändå utanför - Unga vuxnas etablering och anställningsbarhet på arbetsmarknaden - Nemeth,Noemi; Durakovic,Elma (2026)
Youth unemployment and the transition from school to work remain pressing issues in Sweden, despite rising educational levels among young adults. This study explores how young people aged 18-24 with an upper secondary degree and limited work experience perceive their entry into the labour market. What factors shape their chances of being seen as attractive candidates, and how HR-related professionals understand this transition. The study is based on a qualitative research design with a hermeneutic approach and semi-structured interviews with two groups of informants: HR-related staff with recruitment responsibilities and young adults who have recently been job seeking. Thematic analysis was used to identify recurring patterns and tensions in the material. The results show that young adults generally experience the labour market as uncertain, demanding and highly individualised. They describe feelings of being unprepared, left alone to “figure out” how to write CV:s, search for jobs and interpret employers´expectations. HR-related staff emphasise that employability today involves far more than formal education, highlighting personality, social competence, the “right attitude” and prior experience. Social and cultural capital, such as networks and prior practice placements emerge as key resources that open doors, while their absence reinforces perceived unfairness and exclusion. Both groups express that the school system does not adequately prepare young people for the practical and social demands of working life. This contributes to a gap between education and employment. Overall, the study shows that young adults´establishment on the labour market is shaped by a complex interplay between individual resources and structural conditions. Responsibility for employability is largely placed on the individual rather than shared between education, employers and society. Keywords: youth unemployment, employability, social and cultural capital, HR, young adults, Sweden
Keywords: Youth unemployment; employability; social and cultural capital; HR; young adults; Sweden.